Amorphous phase graded hollow microsphere nanomaterial and its preparation method and application
By preparing an amorphous graded hollow microsphere nanomaterials, the low -electricity and reunification problems of transition metal hydroxide electrode materials were solved, and high -ratio, excellent magnification performance, and good structural stability were achieved.
Patent Information
- Application Number
- CN202211271140.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-18
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-10-18
AI Technical Summary
The existing transition metal hydroxide electrode materials have problems such as low conductivity, easy agglomeration, slow electron/ion transfer rates and few active sites, resulting in the actual capacity far below the theoretical value.
Using an amorphous grading hollow microsphere nanomaterial, by dissolving the transition metal salt in the hybrid solvent for the solvent thermal reaction, the transition metal alcohol salt micro -ball front drive was transformed into a transition metal hydroxide grades in the hydrolyzed reactions The hollow microsphere is prepared by the anion exchange reaction to prepare an amorphous phase grading hollow microsphere material.
It improves the electrochemical activity area, capacity, percentage performance and structural stability of the material, significantly improves the electrochemical properties, and solves the problem of poor material impedance and poor circulation stability.
Smart Images

Figure CN115410833B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of new energy storage and conversion, specifically to the field of electrode materials, and in particular to an amorphous phase graded hollow microsphere nanomaterial and a preparation method and application thereof. Background Art
[0002] Transition metal hydroxides with typical layered structures are widely used in supercapacitors due to their advantages such as rich Faraday redox reactions, multiple ion valence states, adjustable components and high theoretical capacity, especially double metal hydroxides, such as nickel cobalt hydroxide, nickel manganese hydroxide, nickel iron hydroxide, etc. However, transition metal hydroxides themselves have defects, namely low electrical conductivity and easy agglomeration, which lead to their sluggish electron / ion transfer rate and limited active sites, making their actual capacity far lower than the theoretical value. In order to solve the defects of transition metal hydroxides, we can start from their structural design and component regulation. Among them, combining the hollow structure with the amorphous phase can make full use of the advantages of both, not only can it effectively promote the diffusion and transfer of electrolyte ions, but also can expose more electrochemically active sites, improve the accessibility between electrochemically active sites and electrolyte ions, and enrich the electrochemical reaction. In addition, the regulation between the components of transition metal hydroxides can optimize their electronic structure, accelerate the transfer of electrons during electrochemical reactions, and reduce material impedance. However, researchers have found that the electrode materials currently prepared rarely combine hollow structure, amorphous phase and component regulation, and the prepared transition hydroxide materials still have problems such as complex process, low specific capacity and poor cycle stability. Summary of the invention
[0003] In order to solve the defects of the prior art and the problems of transition metal hydroxides being easy to agglomerate, having low conductivity, and having few active sites, the purpose of the present invention is to provide an amorphous phase graded hollow microsphere nanomaterial and its preparation method and application. Due to its typical structural advantages and multi-component composition characteristics, the present invention has a higher electrochemical active area, higher specific capacity, excellent rate performance, and good structural stability.
[0004] To achieve the above object, the specific technical solution adopted by the present invention is as follows: A method for preparing amorphous phase graded hollow microsphere nanomaterials, comprising the following steps:
[0005] ① dissolving at least two transition metal salts in a mixed alcohol solvent, stirring for a period of time to fully dissolve them, subjecting the mixed solution to a constant temperature solvent thermal reaction for a period of time, and subjecting the product to centrifugal separation, anhydrous ethanol washing and vacuum drying to obtain a transition metal alkoxide microsphere precursor;
[0006] ② The obtained transition metal alkoxide microspheres are dispersed in deionized water, subjected to ultrasonic treatment, and subjected to constant temperature hydrolysis reaction for a period of time. The product is subjected to centrifugal separation, deionized water washing and vacuum drying to obtain transition metal hydroxide graded hollow microsphere materials;
[0007] ③ The prepared transition metal hydroxide graded hollow microspheres are dispersed in an anion exchange solution, subjected to ultrasonic treatment, stirred and reacted at room temperature for a period of time, and the product is subjected to centrifugal separation, deionized water washing and vacuum drying to obtain an amorphous transition metal graded hollow microsphere material.
[0008] As a further improvement of the technical solution of the present invention, the isothermal solvent thermal reaction temperature is 150-180°C, and the reaction time is 1-8h.
[0009] As a further improvement of the technical solution of the present invention, the isothermal hydrolysis reaction temperature is 60-160° C., and the reaction time is 0.5-8 h.
[0010] As a further improvement of the technical solution of the present invention, the anion exchange solution is a sodium hypophosphite aqueous solution, a sodium phosphate aqueous solution or a sodium sulfide aqueous solution.
[0011] As a further improvement of the technical solution of the present invention, the transition metal salt is nickel nitrate, cobalt nitrate, manganese nitrate, iron nitrate, copper nitrate or molybdenum acetylacetonate.
[0012] As a further improvement of the technical solution of the present invention, the mixed alcohol solvent is composed of a polyol and a monool, and the volume ratio of the polyol to the monool is 1:4 to 1:10.
[0013] As a further improvement of the technical solution of the present invention, the polyol is one or more of a linear diol, a nonlinear diol, propylene glycol, and trimethylolpropane; the monohydric alcohol is one or more of methanol, ethanol, and isopropanol.
[0014] The present invention further provides amorphous phase graded hollow microsphere nanomaterial obtained by the preparation method.
[0015] As a further improvement of the technical solution of the amorphous phase graded hollow microsphere nanomaterial of the present invention, the shell layer of the amorphous phase graded hollow microsphere nanomaterial is constructed by amorphous phase nanosheets, the interior is a hollow structure, and the amorphous phase nanosheets contain transition metal cations and anions.
[0016] The present invention also provides application of the amorphous phase graded hollow microsphere nanomaterial obtained by the preparation method as a supercapacitor electrode material.
[0017] Compared with the prior art, the amorphous phase graded hollow microsphere nanomaterial and its preparation method and application in the present invention have the following beneficial effects:
[0018] (1) The present invention uses a transition metal alkoxide microsphere precursor as a self-template, and derives it into hierarchical hollow microspheres constructed of transition metal hydroxide nanosheets through a simple and rapid hydrolysis reaction. This process can effectively avoid the problems of hard template post-treatment (surface treatment, etching, calcination, etc.) and the difficulty in controlling soft template reaction conditions, which is conducive to simplifying the preparation process of hollow structure materials.
[0019] (2) The amorphous phase graded hollow microsphere material prepared by the room temperature anion exchange reaction in the present invention not only maintains the structural advantages of the hollow microspheres, which is beneficial to promote the diffusion and transfer of electrolyte ions, but also the transformed amorphous phase can further increase the specific surface area and electrochemical active area of the material, expose more electrochemical active sites, improve the accessibility between the active sites and the electrolyte ions, and enrich the electrochemical reactions.
[0020] ⑶ In the amorphous phase graded hollow microsphere material prepared by the room temperature anion exchange reaction of the present invention, the introduced double anions can optimize the electronic structure of the material, significantly reduce the band gap, accelerate the charge transfer during the electrochemical redox reaction, and reduce the impedance of the material.
[0021] (4) The amorphous phase graded hollow microsphere material provided by the present invention is used as a supercapacitor positive electrode material, and shows excellent specific capacity, rate performance and cycle stability during electrochemical performance testing. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 This is the XRD spectrum of the amorphous phase graded hollow microsphere NiCo-DHS-12 material prepared in Example 4. It can be seen from the figure that compared with the NiCo-DH material prepared by direct hydrolysis, the XRD diffraction peak of the prepared NiCo-DHS-12 material obviously disappears, showing typical amorphous phase characteristics.
[0024] Figure 2 The SEM and TEM images of the amorphous hierarchical hollow microsphere NiCo-DHS-12 material prepared in Example 4. It can be seen from the figure that after the NiCo-DH material undergoes room temperature ion exchange reaction, the NiCo-DHS-12 material still maintains the morphology of hierarchical hollow microspheres, and has the advantages of both nanosheets (2D structure) and hollow microspheres (3D structure).
[0025] Figure 3 C of the amorphous phase graded hollow microsphere NiCo-DHS-12 material prepared in Example 4 dl It can be seen from the figure that the C values of the amorphous phase graded hollow microsphere NiCo-DHS-12 material and the NiCo-DH material prepared by hydrolysis are fitted. dl The values are 22.41 and 4.56 mFcm respectively -2 , indicating that the amorphous phase introduced into NiCo-DHS-12 material can increase the electrochemical activation area of the material.
[0026] Figure 4 This is the XPS test result of the amorphous phase graded hollow microsphere NiCo-DHS-12 material prepared in Example 4. It can be seen from the figure that the signal peak of the S element appears in the amorphous phase graded hollow microsphere NiCo-DHS-12 material, indicating that OH - ions (NiCo-DH material) are partially replaced by S 2- is replaced to form the final hydroxy sulfide.
[0027] Figure 5 This is the rate performance diagram of the amorphous phase graded hollow microsphere NiCo-DHS-12 material prepared in Example 4. It can be seen from the figure that when the current density increases to 30 A g -1 When the direct hydrolysis NiCo-DH electrode material (specific capacity of 605 Cg -1 , 1 A g -1 ) and amorphous phase graded hollow microsphere NiCo-DHS-12 electrode material (specific capacity 973 C g -1 , 1 A g -1 ) have specific capacities of 357.1 and 716.5 C g -1 Correspondingly, the capacitance retention rates of NiCo-DH and NiCo-DHS-2 electrode materials are 73.6% and 59.0%, respectively. The rate performance of NiCo-DHS-12 electrode material is significantly higher than that of NiCo-DH electrode material.
[0028] Figure 6 The cyclic stability diagram of the amorphous phase graded hollow microsphere NiCo-DHS-12 material prepared in Example 4. It can be seen from the figure that after 8000 consecutive charge and discharge cycles (current density of 10 A g -1 ), the Coulombic efficiency and capacity retention rate of NiCo-DHS-12 electrode material were 99.29% and 94.1%, respectively, showing high cycle structural stability. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The present invention provides a specific embodiment of a method for preparing an amorphous phase graded hollow microsphere nanomaterial, comprising the following steps:
[0031] ① dissolving at least two transition metal salts in a mixed alcohol solvent, stirring for a period of time to fully dissolve them, subjecting the mixed solution to a constant temperature solvent thermal reaction for a period of time, and subjecting the product to centrifugal separation, anhydrous ethanol washing and vacuum drying to obtain a transition metal alkoxide microsphere precursor;
[0032] ② The obtained transition metal alkoxide microspheres are dispersed in deionized water, subjected to ultrasonic treatment, and subjected to constant temperature hydrolysis reaction for a period of time. The product is subjected to centrifugal separation, deionized water washing and vacuum drying to obtain transition metal hydroxide graded hollow microsphere materials;
[0033] ③ The prepared transition metal hydroxide graded hollow microspheres are dispersed in an anion exchange solution, subjected to ultrasonic treatment, stirred and reacted at room temperature for a period of time, and the product is subjected to centrifugal separation, deionized water washing and vacuum drying to obtain an amorphous transition metal graded hollow microsphere material.
[0034] In one embodiment provided by the present invention, in step ①, the transition metal salt is nickel nitrate (Ni(NO3)2∙6H2O), cobalt nitrate (Co(NO3)2∙6H2O), manganese nitrate (Mn(NO3)2∙6H2O), iron nitrate (Fe(NO3)3∙9H2O), copper nitrate (Cu(NO3)2∙3H2O) or molybdenum acetylacetonate ((CH3COCHCOCH3)MoO2). In step ①, the transition metal salt dissolved in the mixed alcohol solvent is two or more of the aforementioned transition metal salts. The preferred two transition metal salts are nickel nitrate (Ni(NO3)2∙6H2O) and cobalt nitrate (Co(NO3)2∙6H2O), wherein the molar ratio of nickel nitrate (Ni(NO3)2∙6H2O) to cobalt nitrate (Co(NO3)2∙6H2O) is preferably 1:1~1:4.
[0035] In another embodiment provided by the present invention, the mixed alcohol solvent is composed of a polyol and a monool, and the volume ratio of the polyol to the monool is 1:4 to 1:10. In this embodiment, the polyol in the mixed alcohol solvent serves as a chelating agent, and the monool serves as a solvent. Among them, the polyol is one or more of a linear diol, a nonlinear diol, propylene glycol, and trimethylolpropane; the monool is one or more of methanol, ethanol, and isopropanol. Specifically, the linear diol includes ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, etc.; the nonlinear diol includes 1,2-propylene glycol, 1,2-butanediol, 1,3-propylene glycol, etc. The preferred chelating agent is isopropanol, the preferred solvent is ethanol or isopropanol, and the preferred volume ratio of the chelating agent to the solvent is 1:5 to 1:7.
[0036] In one embodiment provided by the present invention, the isothermal solvent thermal reaction temperature is 150-180 ° C, and the reaction time is 1-8 hours. Preferably, the isothermal solvent thermal reaction temperature is 160-180 ° C, and the preferred reaction time is 6-8 hours. The present invention does not particularly limit the equipment for the isothermal solvent thermal reaction, and is preferably a stainless steel hydrothermal kettle. The product of the isothermal solvent thermal reaction needs to be centrifuged, washed with anhydrous ethanol and vacuum dried until the product is constant weight. The preferred vacuum drying temperature is 60-80 ° C, and the preferred vacuum drying time is 8-12 hours.
[0037] In another embodiment provided by the present invention, in step ②, the diameter of the transition metal alkoxide microsphere precursor is 400~700nm. Specifically, when the transition metal alkoxide microsphere precursor is dispersed in deionized water, the mass ratio of the metal alkoxide microsphere precursor to deionized water is 1:100~1:1000. Preferably, the ultrasonic treatment time is 5~10min, and the ultrasonic treatment power is 80 W. The constant temperature hydrolysis reaction temperature is 60~160℃, and the reaction time is 0.5~8h. The preferred constant temperature hydrolysis reaction temperature is 120~160℃, and the preferred reaction time is 4~7h. The present invention does not particularly limit the equipment for the constant temperature hydrolysis reaction, and is preferably a stainless steel hydrothermal kettle. Similarly, the product of the constant temperature hydrolysis reaction needs to be centrifuged, washed with deionized water, and vacuum dried until the product is constant weight. The preferred vacuum drying treatment temperature is 60~80℃, and the preferred vacuum drying treatment time is 8~12h.
[0038] In one embodiment provided by the present invention, in step ③, the anion exchange solution is a sodium hypophosphite (NaH2PO2) aqueous solution, a sodium phosphate (Na3PO4) aqueous solution or a sodium sulfide (Na2S) aqueous solution. When the transition metal hydroxide graded hollow microspheres are dispersed in the anion exchange solution, when the transition metal hydroxide graded hollow microsphere material dosage is 10~200mg, the concentration and volume of the anion exchange solution are 0.5~6mol / L and 10~100mL, respectively, and the stirring reaction time at room temperature is 0.5~72h. Preferably, the transition metal hydroxide graded hollow microsphere material dosage is 50~100mg, the concentration and volume of the anion exchange solution are preferably 1~4 mol / L and 30~50mL, respectively, and the stirring reaction time at room temperature is preferably 6~36h. Similarly, the product after the transition metal hydroxide graded hollow microsphere material is dispersed in the anion exchange solution needs to be centrifuged, washed with deionized water, and vacuum dried, and vacuum dried to a constant weight of the product. The preferred vacuum drying treatment temperature is 60-80°C, and the preferred vacuum drying treatment time is 8-12 hours.
[0039] The present invention also provides an amorphous phase graded hollow microsphere nanomaterial obtained by any of the above preparation methods. The shell of the amorphous phase graded hollow microsphere nanomaterial is constructed by amorphous phase nanosheets, the interior is a hollow structure, and the amorphous phase nanosheets contain transition metal cations and anions.
[0040] In one embodiment provided by the present invention, the diameter of the amorphous phase graded hollow microspheres is 500-900 nm, and the thickness of the nanosheets is 8-20 nm.
[0041] The present invention also provides the application of the amorphous phase graded hollow microsphere nano material as a supercapacitor electrode material.
[0042] The technical solution of the present invention is described in detail below through specific embodiments.
[0043] Example 1
[0044] 72.6 mg Ni(NO3)2∙6H2O and 72.6 mg Co(NO3)2∙6H2O were weighed and dissolved in 48 mL of propylene glycol / ethanol (mixed alcohol solvent, the volume ratio of chelating agent to solvent was 1:5) mixed solvent. The solution was transferred to a stainless steel hydrothermal autoclave and kept at 160 °C for 6 h. After the hydrothermal autoclave was naturally cooled to room temperature, the product was centrifuged, washed with anhydrous ethanol and vacuum dried (dried at 80 °C for 8 h) to obtain a nickel cobalt alkoxide microsphere precursor.
[0045] Example 2
[0046] 72.6 mg Ni(NO3)2∙6H2O and 145.2 mg Co(NO3)2∙6H2O were weighed and dissolved in 70 mL of glycerol / isopropanol (mixed alcohol solvent, the volume ratio of chelating agent to solvent was 1:6) mixed solvent. The solution was transferred to a stainless steel hydrothermal autoclave and kept at 160 °C for 8 h. After the hydrothermal autoclave was naturally cooled to room temperature, the product was centrifuged, washed with anhydrous ethanol and vacuum dried (dried at 80 °C for 8 h) to obtain a nickel cobalt alkoxide microsphere precursor.
[0047] Example 3
[0048] Weigh 50 mg of the nickel cobalt alkoxide microsphere precursor prepared in Example 2 and disperse it in 30 mL of deionized water. Ultrasonic treatment was performed for 5 min at an ultrasonic power of 80 W. The dispersion was transferred to a stainless steel hydrothermal kettle and kept at 140 ° C for 4 h. After the hydrothermal kettle was naturally cooled to room temperature, the product was centrifuged, washed with anhydrous ethanol and vacuum dried (dried at 80 ° C for 8 h) to obtain a light green nickel cobalt hydroxide graded hollow microsphere material (NiCo-DH). At the same time, the NiCo-DH material was analyzed by X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). The corresponding results are shown in Figure 1 .
[0049] The NiCo-DH, acetylene black and polyvinylidene fluoride prepared in this example were placed in an agate mortar in a mass ratio of 8:1:1, and a small amount of N-methylpyrrolidone was added. The slurry electrode material was fully ground and evenly coated on the clean nickel foam surface. The coating area was 1×1 cm 2 After vacuum drying, the coated nickel foam (electrode sheet) was flattened with a pressure of 10 MPa, and the mass before and after coating was weighed. The corresponding active material loading was calculated to be about 2~3 mg; a three-electrode system was constructed with the prepared working electrode, Hg / HgO and platinum sheet, and 3 M KOH solution was used as the electrolyte to test the electrochemical performance of the NiCo-DH material. According to its charge and discharge curves, it can be obtained that the active material loading at 1, 2, 3, 5, 7, 10, 15, 20 and 30 A g -1 The specific capacities at the current densities are 605, 575, 553, 517.5, 486.7, 455, 420.5, 388, and 357.1 C g, respectively. -1 Specific results such as Figure 5 shown.
[0050] Example 4
[0051] Weigh 30 mg of the NiCo-DH material prepared in Example 3 and disperse it in a 2 mol / L Na2S aqueous solution (50 mL), ultrasonically treat for 5 min, the ultrasonic power is 80 W, and react at room temperature for 12 h. The product is centrifuged, washed with deionized water, and vacuum dried (80 ° C for 8 h) to obtain a black amorphous nickel cobalt hydroxysulfide graded hollow microsphere material (NiCo-DHS-12). At the same time, the NiCo-DHS-12 material is characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction analysis (XRD) and X-ray photoelectron spectroscopy analysis. The corresponding results are shown in Figure 1 , Figure 2 and Figure 3 .
[0052] The NiCo-DHS-12, acetylene black and polyvinylidene fluoride prepared in this example were placed in an agate mortar in a mass ratio of 8:1:1, and a small amount of N-methylpyrrolidone was added. The slurry electrode material was fully ground and evenly coated on the clean nickel foam surface. The coating area was 1×1 cm 2 After vacuum drying, the coated nickel foam (electrode sheet) was flattened with a pressure of 10 MPa, and the mass before and after coating was weighed. The corresponding active material loading was calculated to be about 2~3 mg; a three-electrode test system was constructed with the prepared working electrode, Hg / HgO and platinum sheet, and 3 M KOH solution was used as the electrolyte to test the electrochemical performance of NiCo-DHS-12 material. According to its charge and discharge curves, it can be obtained that at 1, 2, 3, 5, 7, 10, 15, 20 and 30 A g -1 The specific capacities at the current densities are 973, 942, 922.9, 890, 860.5, 827, 794, 760, and 716.5 C g, respectively. -1 , the specific results are as follows Figure 5 shown.
[0053] In addition, at 10 A g -1 The NiCo-DHS-12 material was continuously charged and discharged for 8000 times at a current density of Figure 6 After 8000 cycles of continuous charge and discharge, the specific capacity retention rate and coulombic efficiency of NiCo-DHS-12 material were 94.1% and 99.29%, respectively, indicating that it has high cycle stability.
[0054] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing amorphous phase graded hollow microsphere nanomaterials, characterized in that: The steps include: ① dissolving at least two transition metal salts in a mixed alcohol solvent, stirring for a period of time to fully dissolve them, subjecting the mixed solution to a constant temperature solvothermal reaction for a period of time, and subjecting the product to centrifugal separation, anhydrous ethanol washing and vacuum drying to obtain a transition metal alkoxide microsphere precursor; the constant temperature solvothermal reaction temperature is 150-180°C, and the reaction time is 1-8h; ② The obtained transition metal alkoxide microspheres are dispersed in deionized water, subjected to ultrasonic treatment, and subjected to constant temperature hydrolysis reaction for a period of time. The product is subjected to centrifugal separation, deionized water washing and vacuum drying to obtain transition metal hydroxide graded hollow microsphere materials; the constant temperature hydrolysis reaction temperature is 60-160°C, and the reaction time is 0.5-8h; ③ Dispersing the prepared transition metal hydroxide graded hollow microspheres into an anion exchange solution, ultrasonically treating, stirring and reacting at room temperature for a period of time, and centrifugally separating the product, washing with deionized water and vacuum drying to obtain an amorphous transition metal graded hollow microsphere material; The anion exchange solution is a sodium hypophosphite aqueous solution or a sodium phosphate aqueous solution.
2. The method for preparing amorphous phase graded hollow microsphere nanomaterial according to claim 1, characterized in that: The transition metal salt is nickel nitrate, cobalt nitrate, manganese nitrate, iron nitrate, copper nitrate or molybdenum acetylacetonate.
3. The method for preparing amorphous phase graded hollow microsphere nanomaterial according to claim 1, characterized in that: The mixed alcohol solvent is composed of polyol and monool, and the volume ratio of the polyol to the monool is 1:4-1:
10.
4. The method for preparing amorphous phase graded hollow microsphere nanomaterial according to claim 3, characterized in that: The polyol is one or more of a linear diol, a nonlinear diol, propylene glycol, and trimethylolpropane; the monohydric alcohol is one or more of methanol, ethanol, and isopropanol.
5. Amorphous phase graded hollow microsphere nanomaterial obtained by the preparation method according to any one of claims 1 to 4.
6. The amorphous phase graded hollow microsphere nanomaterial according to claim 5, characterized in that: The shell layer of the amorphous phase graded hollow microsphere nanomaterial is constructed by amorphous phase nanosheets, the interior is a hollow structure, and the amorphous phase nanosheets contain transition metal cations and anions.
7. Use of the amorphous phase graded hollow microsphere nanomaterial obtained by the preparation method according to any one of claims 1 to 4 as a supercapacitor electrode material.
Citation Information
Patent Citations
Phosphide with hierarchical structure, and preparation method and applications thereof
CN109956458A
Alkali-sulfur composite treatment method for cobalt-chromium-nickel hydrotalcite supercapacitor electrode material
CN113307312A